2010
DOI: 10.2478/s11535-009-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of chitosan oligosaccharides in RAW 264.7 cells

Abstract: Anti-inflammatory effect of chitosan oligosaccharides in RAW 264.7 cells * E-mail: cghyun@jejuhidi.or.kr Abstract: We examined the effects of chitosan oligosaccharides (COSs) with different molecular weights (COS-A, 10 kDa < MW < 20 kDa; COS-C, 1 kDa < MW < 3 kDa) on the lipopolysaccharide (LPS)-induced production of prostaglandin E 2 and nitric oxide and on the expression of cyclooxygenase-2 and inducible nitric oxide synthase in RAW264.7 macrophages. COS-A (0.4%) and COS-C (0.2%) significantly inhibited PGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 33 publications
(34 reference statements)
1
33
0
4
Order By: Relevance
“…Elevated levels of interleukin-1 and other cytokines activate the expression of NO synthesis, which produces high levels of NO free radicals (Mandrup-Poulsen et al, 1985). Studies have shown chitosan oligosaccharide exerts anti-inflammatory effects by inhibiting the formation of NO in macrophages (Yang et al, 2010). One of the possible mechanisms of damage to b cells in the STZ induction diabetes may be NO overproduction, which is followed by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of interleukin-1 and other cytokines activate the expression of NO synthesis, which produces high levels of NO free radicals (Mandrup-Poulsen et al, 1985). Studies have shown chitosan oligosaccharide exerts anti-inflammatory effects by inhibiting the formation of NO in macrophages (Yang et al, 2010). One of the possible mechanisms of damage to b cells in the STZ induction diabetes may be NO overproduction, which is followed by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…CCA P. acnes HaCaT cell 50 g/mL, 100 g/mL 300 g/mL , 40%, 55% 65% NO . chitosan RAW 264.7 cell 44.1%-50.2% NO Yang et al (2010) . Chitosan NO inducible nitric oxide synthase (iNOS) .…”
Section: P Acnes에 의해 염증 유도된mentioning
confidence: 99%
“…Chitin and chitosan have excellent properties, such as biodegradability, biocompatibility and non-toxicity adsorption (Majeti and Kumar, 2000). Chitosan and its oligomers are known for its various important biological properties such as antimicrobial (Park et al, 2015), antifungal (Hussain et al, 2012), antioxidant (Younes and Rinaudo, 2015), neuroprotective (Pangestuti and Kim, 2010) and anti-inflammatory (Yang et al, 2010). Besides having versatile biological functions, major drawbacks in application of chitosan is its insolubility in water and high molecular weight (Shen et al 2009).…”
Section: Introductionmentioning
confidence: 99%